Poverty, Social Divisions, and Conflict in Nepal - Do, Quy-Toan; Iyer, Lakshmi (World Bank, Washington, DC, 2012)
The authors conduct an econometric analysis of the economic and social factors which contributed to the spread of violent conflict in Nepal. They find that conflict intensity is significantly higher in places with greater poverty and lower levels of economic development. Violence is higher in locations that favor insurgents, such as mountains and forests. The authors find weaker evidence that caste divisions in society are correlated with the intensity of civil conflict, while linguistic diversity has little impact.